2021
DOI: 10.5798/dicletip.887421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hematological inflammatory parameters in patients with exfoliative glaucoma and exfoliative syndrome

Abstract: Objective: To evaluate the neutrophil / lymphocyte ratio (NLR), platelet / lymphocyte ratio (PLR), and systemic immune inflammation index (SII) in exfoliative glaucoma (XFG) patients with the aim of comparing the findings with those of healthy controls and exfoliative syndrome (XFS) patients. Methods:In this retrospective cross-sectional study included 134 participants, 22 XFG patients, 41 XFS patients and 71 healthy individuals were examined. Peripheral venous sample values including neutrophil, lymphocyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…We found six studies on KC [ 5 , 11 , 13 , 15 , 23 , 27 ], six studies on pterygium [ 12 , 16 , 17 , 19 , 22 , 35 ], four studies on DED [ 6 , 21 , 24 , 28 ], and four studies on iERM [ 7 , 8 , 10 , 30 ]. Also, the association between NLR and glaucoma was investigated in 12 studies [ 3 , 4 , 9 , 14 , 18 , 20 , 25 , 26 , 29 , 31 , 37 , 38 ], of which four were conducted among East Asian patients [ 20 , 29 , 31 , 38 ] and eight among Caucasian patients [ 3 , 4 , 9 , 14 , 18 , 25 , 26 , 37 ]. Among these ten studies, we found five studies on POAG [ 3 , 4 , 14 , 25 , 29 ], six studies on SOAG [ 3 , 9 , 18 , 26 , 37 , 38 ], two studies on PCAG [ 14 , 20 ], and one study on SCAG [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found six studies on KC [ 5 , 11 , 13 , 15 , 23 , 27 ], six studies on pterygium [ 12 , 16 , 17 , 19 , 22 , 35 ], four studies on DED [ 6 , 21 , 24 , 28 ], and four studies on iERM [ 7 , 8 , 10 , 30 ]. Also, the association between NLR and glaucoma was investigated in 12 studies [ 3 , 4 , 9 , 14 , 18 , 20 , 25 , 26 , 29 , 31 , 37 , 38 ], of which four were conducted among East Asian patients [ 20 , 29 , 31 , 38 ] and eight among Caucasian patients [ 3 , 4 , 9 , 14 , 18 , 25 , 26 , 37 ]. Among these ten studies, we found five studies on POAG [ 3 , 4 , 14 , 25 , 29 ], six studies on SOAG [ 3 , 9 , 18 , 26 , 37 , 38 ], two studies on PCAG [ 14 , 20 ], and one study on SCAG [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between NLR and glaucoma was investigated in 12 studies [ 3 , 4 , 9 , 14 , 18 , 20 , 25 , 26 , 29 , 31 , 37 , 38 ] including 1568 glaucoma patients and 1737 healthy controls. NLR levels were significantly higher in glaucoma patients compared with controls (SMD =0.56; 95% CI =0.25-0.87, P < 0.001) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations